Determining Acute Leukemia Lineage Using Mie Map Red Blood Cell - Nelly Zuroidah; Arifoel Hajat; Paulus Budiono Notopuro (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
The determination of myeloid and lymphoid lineage is essential for the diagnosis and therapy of acute leukemia. Immunophenotyping is the gold standard to determine the lineage of acute leukemia, but it is still constrained and relatively expensive. Mie Map RBC in the ADVIA 2120i is a parameter that can give additional information about myeloid and lymphoid lineage but has never been studied before. It is expected that Mie Map RBC can be used to differentiate the lineage of acute myeloid and lymphoid leukemia if immunophenotyping is not present. This study aimed to analyze the diagnostic value of Mie Map RBC with ADVIA 2120i towards immunophenotyping in determining myeloid and lymphoid lineage in acute leukemia. Child and adult patients diagnosed with acute leukemia (n=30) that had peripheral blood smear and bone marrow aspiration with blasts > 20% were examined using ADVIA 2120i. The Mie Map RBC lineage results were compared to the lineage of immunophenotyping. The sensitivity and specificity of the Mie Map RBC myeloid series are respectively 60.00%, 93.33%. The sensitivity and specificity of the Mie Map RBC lymphoid series are respectively 93.33% and 60.00%. The diagnostic accuracy value of Mie Map RBC is 76.67%. The determination of acute leukemia myeloid series lineage has high specificity. If there is no population outside the matrix of Mie Map RBC, it highly suggests myeloid series. On the other hand, the determination of acute leukemia lymphoid series lineage has a relatively low specificity meaning that the population outside the matrix of Mie Map RBC does not always suggest a lymphoid lineage